2016
DOI: 10.1159/000448265
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain Polyunsaturated Fatty Acids and Clinical Outcomes of Preterm Infants

Abstract: Long-chain polyunsaturated fatty acids (LCPUFAs) play specific roles during the perinatal period and are very important nutrients to consider. The possible effects of LCPUFAs, particularly docosahexaenoic acid (DHA), on various clinical outcomes of preterm infants are discussed in this paper. Since DHA accumulates in the central nervous system during development, a lot of attention has focused on the effects of DHA on neurodevelopment. Experimental studies as well as recent clinical trials show that providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 66 publications
(85 reference statements)
0
46
0
1
Order By: Relevance
“…Very preterm infants develop a large deficit in DHA as well as in the omega-6 LCPUFA arachidonic acid (AA) during parenteral nutrition with commonly used soybean- [ 7 ] and olive oil-based lipid emulsions [ 8 ] as well as during enteral nutrition even with breastfeeding [ 9 , 10 ]. Lapillonne et al have estimated that an infant born at gestational age (GA) 27 weeks weighing 1000 g will have a DHA deficit of 600 mg/kg at age 4 weeks [ 11 ] which is thought to contribute to preterm morbidities such as bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), necrotizing enterocolitis (NEC) and white matter injury and sepsis [ 12 ]. Supplementation of omega-3 LCPUFA to preterm children was recently reviewed by Zhang et al [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very preterm infants develop a large deficit in DHA as well as in the omega-6 LCPUFA arachidonic acid (AA) during parenteral nutrition with commonly used soybean- [ 7 ] and olive oil-based lipid emulsions [ 8 ] as well as during enteral nutrition even with breastfeeding [ 9 , 10 ]. Lapillonne et al have estimated that an infant born at gestational age (GA) 27 weeks weighing 1000 g will have a DHA deficit of 600 mg/kg at age 4 weeks [ 11 ] which is thought to contribute to preterm morbidities such as bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), necrotizing enterocolitis (NEC) and white matter injury and sepsis [ 12 ]. Supplementation of omega-3 LCPUFA to preterm children was recently reviewed by Zhang et al [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These and other LC‐PUFAs serve as precursors of potent signaling molecules, including prostaglandins, thromboxanes, leukotrienes, and resolvins, with well‐documented roles in inflammation and immune functions . DHA and AA deficiency in neonates has been associated with an altered growth rate, manifestations of allergy, reduced intellectual development, and increased risk of several morbidities commonly associated with prematurity . Preterm infants are capable, to a certain extent, of de novo synthesis of DHA and AA from their shorter‐chain precursors ALA and LA, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Although the most recent Cochrane review did not show any significant effect of LCPUFA supplementation (42), two other recent systematic reviews, Shulkin et al (133) and Wang et al (134) concluded that LCPUFA supplementation in preterm infants has short term neurodevelopmental benefits. Lapillone and Moltu also concluded that there is evidence of short term benefit with a high dose DHA supplement and their review focused on several areas of benefit in preterm development (135). Smith and Rouse published a narrative review in 2017 focused on the role of DHA in preterm infants (136), and Laurizen et al have written an interesting commentary on AA (137).…”
Section: Discussionmentioning
confidence: 99%